Preservation and conservation of the archival materials / Afiq Mohd Shahari - Mohd Shahari, Afiq (2014)
This paper is on the preservation and conservation of the archival materials'. An archive is well known as one of the world's primary information sources. Besides, preservation is the activities associated with maintaining and restoring archival materials for continued access, either in their original physical form or in some other usable state. Meanwhile conservation is the use of chemical and physical procedures in treatment or storage to ensure the preservation of books, manuscripts, records, other documents in order to slow their decay and damage. The presentation in the archives is done by providing proper environmental conditions, storage facilities and appropriate packaging materials in order to protect the records from any damage. On the other hand, conservation is done by using chemicals and professional repair techniques to prevent the further deterioration of the records. It is not limited to paper based documents only, archivist also need consider preserving and conserving records in digital format There are various forms of archival materials such as parchment, vellum, manuscript, microfilm, slide, photograph, machine readable records, and tapes. All these materials need to be preserved and conserved in a right way in order to make it available for continued access.